Global terrorism : challenges and policy options - Katoch, Dhruv C.; Sinha, Shakti; India Foundation
Papers presented at second Counter Terrorism Conference; held at Jaipur, India, during February 02-03, 2016.
"Copyright: India Foundation"--Title page verso.
Includes bibliographical references and index.
Keywords: Terrorism -- South Asia -- Congresses; Terrorism -- Congresses